STRUCTURE TRANSFORMATION IN INDONESIA: PERSPECTIVES FROM THE ECONOMICS AND LABOR IN THE INDUSTRY REVOLUTION 4.0 - Sulistiawati, Rini; Lestari, Nindya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
During the decade, the Indonesians faced many economic challenges. Whether in the form of the industrial revolution 4.0 to the COVID19 pandemic. These challenges have led to economic transformation, starting from the agricultural, industrial, and service sectors. The success of this structural transformation is measured by the contribution of the agricultural, manufacturing, and service sectors to national income and employment. This study aims to analyze the transformation of the economic structure towards national income and employment with the Industrial Revolution 4.0 and Covid 19. This research is explanatory with a non-parametric correlation method. The analytical tool in this study is the Spearman correlation which is used to see changes in the transformation of the economic structure and employment in Indonesia. The type of data used is secondary data from BPS Indonesia. This study divides the economic sector into 17 main sectors by BPS Indonesia. The results showed a change in the structure of the Indonesian economy, although manufacturers were still the sector that contributed the most to Indonesia's national income. This also occurs in employment. There is a change in Indonesia"™s employment structure, although the largest absorption is still in the agricultural sector.JEL: O14, O15, J21.